Penguatan Keterampilan Berpikir Kritis Melalui Pengembangan Bahan Ajar Interaktif PPKn Bermuatan Kearifan Lokal di Sekolah Dasar - Citra Silviani; Umar Abdullah; Ary Purwantiningsih (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to develop interactive teaching materials for Civic Education (PPKn) based on local wisdom as an effort to strengthen critical thinking skills of elementary school students. The background of this research stems from the need for innovation in Civic Education learning that not only emphasizes conceptual understanding, but also fosters the ability to analyze, evaluate, and make decisions grounded in cultural values. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fourth-grade students in an elementary school in Rambutan. The findings revealed that the developed interactive teaching materials obtained a very good level of feasibility based on the assessments of subject matter experts, media experts, and educational practitioners. The implementation of the product in a limited trial indicated a significant improvement in students’ critical thinking skills, as shown by test results and positive responses toward the materials. Therefore, the development of interactive Civic Education teaching materials enriched with local wisdom is proven effective in strengthening critical thinking skills and is highly relevant for use in elementary school learning.